Uzbek-US relations (Eurasian Journal of Humanities and Social Sciences, 2022)
Establishing relations between The United States and the United States, reaching the events of September 11, 2001, and the essence of the Declaration on Strategic Partnership signed between the United States and the United States in 2002. Official visit to the United States in 2018.